Hukum Pidana Internasional Sebagai Hukum Global: Penilaian Pengadilan Hybrid Tribunals - Alif Alif; Kholik Kholik (Hakim, 2024)
This is jurnal focuses on the areas of international criminal law where the influence of global law is most evident, ie. hybrid or international criminal courts. Since many of these courts have closed their doors or advanced in the process, the time is ripe for a preliminary assessment. In addition, the future needs and viability of hybrid courts and crimes under the jurisdiction of the International Criminal Court (ICC) are assessed.